Now its your turn - Birkinshaw, Marie (UK Ladybird Books, 1997)
Comprising three stories, "Now it's your Turn", "The Other Side" and "The School Report", and a collection of word games, this book is designed to teach five and six-year-olds the essential skills of reading.